THE EFFECTIVENESS OF THERAPEUTIC AND PREVENTIVE MEASURES TO SUPPORT HOMEOSTASIS OF THE ORAL CAVITY BEFORE URANOPLASTY IN CHILDREN WITH CLEFT PALATE - P.I. Tkachenko; O.B. Dolenko; S.O. Bilokon; N.M. Lokhmatova; Yu.V. Popelo; N.M. Korotych; K.Yu. Rezvina (Український стоматологічний альманах, 2023)
The scientific publications are constantly active in improving the complexes of therapeutic and preventive measures in children with congenital indivisible palate, which are aimed at improving the quality of their life at all stages of observation. This issue is of particular relevance when it comes to surgery, which requires a well-balanced evaluation of somatic and local status in order to create favorable conditions for healing of the wound after radical uranostaphyloplasty.